Lost virtue professional character development in medical education - Kenny, Nuala P.; Shelton, Wayne N. (Advances in bioethics ;, 2006)
Discusses character formation, ethics, professional character, and other concepts and addresses the interpersonal aspects of physicians as well as the importance of character.